Web-age information management 12th International Conference, WAIM 2011, Wuhan, China, September 14-16, 2011, proceedings - Wang, Haixun (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 12th International Conference on Web-Age Information Management, WAIM 2011, held in Wuhan, China in September 2011. The 53 revised full papers presented together with two abstracts and one full paper of the keynote talks were carefully reviewed and selected from a total of 181 submissions. The papers are organized in topical sections on query processing, uncertain data, socialmedia, semantics, data mining, cloud data, multimedia data, user models, data management, graph data, name disambiguation, performance, temporal data, XML, spatial data and event detection.